Relocating Civil Society in a Politics of Civic‐Driven Change. (5th August 2013) - Fowler, Alan; Biekart, Kees
Abstract : Politics is central to development discourse, yet remains peripheral. Over some twenty years, a civil‐society narrative has not fulfilled its potential to 'bring politics back in'. Reasons can be found in conceptual confusion, in selectivity in donor thinking, in policies towards civil society and in the growth‐driven political economy of NGO‐ism. Remedies for the political lacunae are being sought through a focus on rights, citizenship and leadership that show valuable focused progress. This article examines a comprehensive complement to such efforts referred to as civic‐driven change (CDC). Originating in a grounded empirical approach, the constituent principles and elements of CDC offer a lens that can both sharpen and deepen insights and advance analysis of socio‐political processes.